Abstract Semantic Diffing of Evolving Concurrent Programs - Bouajjani, Ahmed; Enea, Constantin; Lahiri, Shuvendu (Static Analysis Symposium 2017 (SAS'17), 2017)
We present an approach for comparing two closely related concurrent programs, whose goal is to give feedback about interesting differences without relying on user-provided assertions. This approach compares two programs in terms of cross-thread interferences and data-flow, under a parametrized abstraction which can detect any difference in the limit. We introduce a partial order relation between these abstractions such that a program change that leads to a ``smaller'' abstraction is more likely to be regression-free from the perspective of concurrency. On the other hand, incomparable or bigger abstractions, which are an indication of introducing new, possibly undesired, behaviors, lead to succinct explanations of the semantic differences.